‘Temples Devoted to Cold Coffee and Hot Sex’: Coffee Bars and Youth Culture in Postwar Britain - Ellis, Catherine (History compass, 2024)
This article explores contemporary and scholarly perspectives on coffee bars in Britain in the 1950s and 1960s, with a particular focus on themes in the modern history of youth. In the immediate postwar decades, young people in Britain were described as simultaneously angry and apathetic, active troublemakers and passive consumers. Young people's use and abuse of leisure time often grounded these contradictory typologies, and coffee bars attracted particular concern. The consumption of coffee was not new in Britain, but this article focuses on heightened anxieties about the association of coffee bars with unsupervised teen sociability, foreign cultures, the ‘Americanization’ of British culture, and the erosion of ‘community’ after Second World War. A closer examination of coffee bars demonstrates both their significance in contemporary debates about young people and their many connections to recent historical analysis of youth in the postwar period.